2016
DOI: 10.4102/sajp.v72i1.338
|View full text |Cite
|
Sign up to set email alerts
|

Causative factors and rehabilitation of patellar tendinopathy: A systematic review

Abstract: BackgroundPatellar tendinopathy (PT) is a common chronic pathology of the knee, with a high prevalence in athletes and the general population.ObjectivesThe objectives of this article were to systematically investigate all the evidence applicable to the intrinsic and extrinsic causative factors and rehabilitation of PT, and then integrate and link rehabilitation with the main causative factors identified.MethodThe Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed. Vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…A recent systematic review by Morgan, Vuuren, and Coetzee () investigated the risk factors of PT and found that common contributing factors are reduced quadriceps strength, inappropriately progressed training load and/or duration, reduced lower limb flexibility, reduced skill set in the sport, and an inferiorly displaced patella. Many of these risk factors are thus modifiable and preventable through appropriate physiotherapy programmes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review by Morgan, Vuuren, and Coetzee () investigated the risk factors of PT and found that common contributing factors are reduced quadriceps strength, inappropriately progressed training load and/or duration, reduced lower limb flexibility, reduced skill set in the sport, and an inferiorly displaced patella. Many of these risk factors are thus modifiable and preventable through appropriate physiotherapy programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Existing systematic reviews have attempted to evaluate the effectiveness of exercises on PT (Larsson, Käll, & Nilsson‐Helander, ; Morgan et al, ; Rabin, ; Visnes & Bahr, ). Although these reviews suggested sufficient evidence for the implementation of eccentric exercises in the management of PT, these reviews only included studies with eccentric exercises or HSR exercises and have not considered the effectiveness of isometric exercise protocols.…”
Section: Introductionmentioning
confidence: 99%
“…This ensured that results cross-referenced and that all eligible articles were included in the review. This interval was chosen to be a supplementary addition to a previously published systematic review on the causative risk factors and rehabilitation for PT in which articles were selected only up to October 2015 (Morgan, Janse van Vuuren & Coetzee 2016 ). Clinical Sports Medicine (5th edition) by Brukner and Khan ( 2017 ) was used as a basis to identify the words for the Boolean phrases.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Several risk factors have been identified including an increased training load, decreased hamstring flexibility, an inferiorlyplaced patella, and reduced quadriceps strength. 4,5 The majority of these risk factors are modifiable, suggesting there is a strong likelihood that patients can respond positively to therapeutic intervention. 4,5 Despite the frequency of PT, the pathological sequence and contributing factors to the reports of pain and disability are not universally agreed Copyright upon.…”
mentioning
confidence: 99%
“…4,5 The majority of these risk factors are modifiable, suggesting there is a strong likelihood that patients can respond positively to therapeutic intervention. 4,5 Despite the frequency of PT, the pathological sequence and contributing factors to the reports of pain and disability are not universally agreed Copyright upon. Histopathological findings of patients suggest symptoms are not due to the inflammatory response and are rather due to degeneration of the tissue.…”
mentioning
confidence: 99%